PENGARUH PENGAWASAN DAN PENILAIAN KINERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PERKEBUNAN (STUDI KASUS KARYAWAN BAGIAN PRODUKSI PADA PTPN V SEI BUATAN) - Hesti Karmila; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research conducted PTPN V Sei Buatan have location District Of Dayun Sub-Province of Siak Area Mount II Siak Sri Indrapura. This Research aim to know the effecy of supervision and performance appraisal on work productivity Of Shares Produce PTPN V Sei Buatan.In this research method the used quantitative descriptive with program of SPSS ver. 23 windows for. Population in this research employees part of production PTPN V Sei Buatan ( Palm Oil Mill) Kampung of Sawit Permai District Of Dayun Sub-Province of Siak amounting to 58 employees. Sampel this research taken by using method of Simple Random sampling that is amounting to 58 employees. Analysis which used in this research that is Test validity, Test reabilitas, Analyse Linear Regresi Modestly, Analyse Doubled Regresi Liner, Analysis of Determinasi, t test and F test.From result of examination which indicate that supervision have an effect on signifikan to prouktivitas work employees, performance appraisal have an effect on signifikan to employees work productivity, and also supervision and performance appraisal have an effect on by simultan to employees work productivity. Result of calculation known R Squre represent coefficient of determinasi and obtained value of R Squre equal to 0,438. Its meaning, observation and performanc appraisal influence employees work productivity equal to 43,80%.Keyword : supervision, Performance appraisal, Employees work productivity